The circadian rhythm of corticosteroid‐binding globulin has little impact on cortisol exposure after hydrocortisone dosing. (9th April 2019) - Melin, Johanna; Hartung, Niklas; Parra‐Guillen, Zinnia P.; Whitaker, Martin J.; Ross, Richard J.; Kloft, Charlotte
Summary: Context: Optimization of hydrocortisone replacement therapy is important to prevent under‐ and over dosing. Hydrocortisone pharmacokinetics is complex as circulating cortisol is protein bound mainly to corticosteroid‐binding globulin (CBG) that has a circadian rhythm. Objective: A detailed analysis of the CBG circadian rhythm and its impact on cortisol exposure after hydrocortisone administration. Design and Methods: CBG was measured over 24 hours in 14 healthy individuals and, employing a modelling and simulation approach using a semi‐mechanistic hydrocortisone pharmacokinetic model, we evaluated the impact on cortisol exposure (area under concentration‐time curve and maximum concentration of total cortisol) of hydrocortisone administration at different clock times and of the changing CBG concentrations. Results: The circadian rhythm of CBG was well described with two cosine terms added to the baseline of CBG: baseline CBG was 21.8 µg/mL and interindividual variability 11.9%; the amplitude for the 24 and 12 hours cosine functions were relatively small (24 hours: 5.53%, 12 hours: 2.87%) and highest and lowest CBG were measured at 18:00 and 02:00, respectively. In simulations, the lowest cortisol exposure was observed after administration of hydrocortisone at 23:00‐02:00, whereas the highest was observed at 15:00‐18:00. The differences between the highest and lowest exposure were minor (≤12.2%), also regarding the free cortisol concentration and free fraction (≤11.7%). Conclusions: Corticosteroid‐binding globulin has a circadian rhythm but the difference in cortisol exposure is ≤12.2% between times of highest and lowest CBG concentrations; therefore, hydrocortisone dose adjustment based on time of dosing to adjust for the CBG concentrations is unlikely to be of clinical benefit.